2013
DOI: 10.1002/app.40240
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cell proliferation in salt‐leaching using powder (SLUP) scaffolds with penetrated macro‐pores

Abstract: In this study, a salt-leaching using powder (SLUP) scaffold with penetrated macropores was proposed to enhance cell proliferation. A SLUP scaffold is a salt-leaching scaffold with an arbitrary pore configuration. Although SLUP scaffolds have several advantage over traditional salt-leaching scaffolds, the cell ingrowth might be poor compared with solid freeform fabrication scaffolds, which have well-interconnected pores. We therefore proposed SLUP scaffolds with penetrated macropores to assist the cell ingrowth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 24 publications
3
10
0
Order By: Relevance
“…The random pore scaffolds were fabricated using salt leaching process as described previously [9,12]. 10 g of NaCl was mixed with 1 ml of water on a 100 mm plastic petri plate as described above.…”
Section: Mould Fabricationmentioning
confidence: 99%
See 4 more Smart Citations
“…The random pore scaffolds were fabricated using salt leaching process as described previously [9,12]. 10 g of NaCl was mixed with 1 ml of water on a 100 mm plastic petri plate as described above.…”
Section: Mould Fabricationmentioning
confidence: 99%
“…Therefore, there is a need for a second type of porous structure, which can efficiently interconnects local random pores of the scaffold for better generation of large tissues under in vitro and in vivo conditions. Recently, studies using dual-pore scaffolds, comprising structured pores (channels) in combination with local random porous regions, have shown tremendous potential towards engineering of complex tissues with better cell proliferation due to improved nutrient and oxygen transport [3,[11][12][13][14][15][16]. A recent report also demonstrated that after transplantation of dual-porous scaffolds more cells from the host tissue infiltrated into the scaffolds due to its smart global pore architecture compared to random porous scaffolds, hence, enhancing integration of blood vessels in the host tissue [17].…”
mentioning
confidence: 99%
See 3 more Smart Citations